2019
DOI: 10.1021/acsami.8b21003
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Enhancement of Silicon Membranes by Ultrathin Amorphous Films

Abstract: We propose a simple, low-cost, and large-area method to increase the thermoelectric figure of merit (ZT) in silicon membranes by the deposition of an ultrathin aluminum layer. Transmission electron microscopy showed that short deposition of aluminum on a silicon substrate covers the surface with an ultrathin amorphous film, which, according to recent theoretical works, efficiently destroys phonon wave packets. As a result, we measured 30−40% lower thermal conductivity in silicon membranes covered with aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The thermal conductivity for the doped sample is lower than the k = 55 Wm −1 K −1 as described in other studies, due to the high concentration of aluminum dopant (Fig. 14a) [84]. This reduction can be attributed to the change in phonon boundary scattering due to the amorphous aluminum layer.…”
Section: The Thermoelectric Power Of Silicon Membranementioning
confidence: 50%
See 2 more Smart Citations
“…The thermal conductivity for the doped sample is lower than the k = 55 Wm −1 K −1 as described in other studies, due to the high concentration of aluminum dopant (Fig. 14a) [84]. This reduction can be attributed to the change in phonon boundary scattering due to the amorphous aluminum layer.…”
Section: The Thermoelectric Power Of Silicon Membranementioning
confidence: 50%
“…Researchers are continuously looking for ways to increase the ZT of silicon and silicon-based materials [84]. The thermoelectric power of the silicon membrane is much lower (ZT of ~ 0.001) than that of common carbon-based composites and alloys that are widely employed for energy harvesters.…”
Section: The Thermoelectric Power Of Silicon Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Our samples were fabricated using the standard topdown fabrication methods on a silicon-on-insulator wafer. The wafer had a top 145-nm-thick monocrystalline silicon layer with atomically smooth (σ = 0.2 nm) top and bottom surfaces [15,16] First, we deposited aluminum pads on the surface of silicon. Next, we used electron-beam Comparison of the predictions of the original seminumerical approach proposed by Hao et al [13] with those of our fully analytical method.…”
Section: B Sample Fabricationmentioning
confidence: 99%
“…78 George et al further demonstrated a 30-40% lower thermal conductivity in silicon membranes covered with aluminum films, leading to significantly enhanced thermoelectric performance. 79 Figure 5 shows the measured in-plane 𝑘 𝐿 of four DRIE-drilled samples and two FIB-drilled samples. 66 Based on the TEM and SEM studies, the pore radius is expanded by 13-40 nm for DRIE samples with pore diameters of 94 to 300 nm, and ~50 nm for FIB samples with pore diameters of 200 and 300 nm.…”
Section: Summary Of Existing Thermal Measurements On Periodic Nanopor...mentioning
confidence: 99%